Patterns of Pregnancy Care Based on Indonesian Culture - Tunggadewi, Ayudya Prameswari; Devi, Shrimarti Rukmini; Soedirham, Oedojo (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2024)
Background: The health of pregnant women is one of the nation’s health indicators. Maternal mortality rate (MMR) and infant mortality rate (IMR) are important indicators to assess a country's welfare and public health conditions. The majority of infant mortality occurs during the neonatal period, which is related to the mother’s health during pregnancy, the awareness of the mother and family about the importance of antenatal care, the participation of health workers, and the availability of medical facilities. In addition, communities in some regions still believe in myths and have a culture that is contrary to the health sciences, which has an impact on the health of pregnant women. This study aims to describe the pattern of pregnancy care in Indonesia.Method: This study is a literature review study. In the data identification process, a total of 263 articles were identified and filtered based on inclusion criteria, language, and research location. Then, the relevant research articles were extracted, sequenced, and examined to identify the subtopics and topics. After the screening and eligibility process, 14 relevant final articles were selected.Results: This study is a literature review study. In the data identification process, a total of 263 articles were identified and filtered based on inclusion criteria, language, and research location. Then, the relevant research articles were extracted, sequenced, and examined to identify the subtopics and topics. After the screening and eligibility process, 14 relevant final articles were selected.